Dormência e pré-germinação de sementes de arroz - Franzin, Simone Medianeira (2006)
Several causes are pointed as responsible for the numbness in seeds of rice. The fenolic compounds have influence in the swinging between promoters and inhibitors of the germination of seeds, could represent an obstacle to the diffusion of gases. Several treatments are used with the purpose of overcoming the dormence in seeds and alternative methods appear to try to solve this problem, as the ultrasound radiations. That technique, for being little used in seeds, however, it presents optimization difficulty, as well as the lack of specific knowledge about the action of the radiation promoted by the ultrasonic waves in living tissues. The objective of the work was to evaluate the chemical effects produced by the ultrasound about the overcoming of the dormence and physiologic quality of seeds of rice. Seeds of irrigated rice cv. IRGA 417 and of drier cv. Spring, submitted to the exhibition of the ultrasonic waves by periods of 5, 10, 15 and 20 minutes and temperatures of 20, 30 and 40 oC. The variables analyzed after each treatment were: germination, first counting and index of germination speed. The results indicated that there was variation in the answers of the culture to the treatments, and the best results were found in the highest temperatures. It was concluded that the ultrasound radiations affect the quality of the seeds of rice, being a promising method for the overcoming of the dormence, still needing her standardization.